Tindakan Hukum Yang Di Lakukan Oleh Pelaku Usaha Terkait Kerugian Yang Di Akibatkan Oleh Orderan Fiktif - Moh Aditya Adjara; Mutia Cherawaty Thalib; Dolot Alhasni Bakung (Lembaga Pengembangan Kinerja Dosen, 2024)
The purpose of this study leads to legal action that can be done by business actors related to losses caused by fictitious orders and legal protection against business actors in online buying and selling transactions Cash on Delivery (COD) payment methods. This type of research is a juridical normative research that leads to legal norms, legal principles and using the statute approach (legislation) and supported by the fact approach (the Fact Approach) and conceptual approach (concept approach). The results of the study that the form of legal protection against business actors who are harmed by consumers is in the form of compensation and/or sanctions against consumers when consumers still do not replace the losses as intended. Although Chapter 13 of the UUPK does not specify criminal sanctions against consumers in particular, this does not mean that consumers can avoid criminal sanctions. Criminal sanctions can be imposed against consumers if the consumer's actions have met the criminal elements. The legal action of business actors against consumers who make fictitious orders can then implement the principle of strict liability, business actors who feel aggrieved over the actions of consumers who are not responsible for the goods that have been ordered can demand compensation or compensation without having to dispute the presence or absence of elements of error on the part of consumers. The threat of punishment obtained against consumers who are proven to have committed fraud will be subject to imprisonment for a maximum of four years in accordance with Article 378 of the Criminal Code.. Therefore, it should pay more attention to legal certainty regarding legal protection not only to consumers but also to business actors. Because basically losses can not only be experienced by consumers but can also be experienced by business actors.